Influences of depression and loneliness towards binge-watching behavior among university students - Yii Shi Si; Patricia Joseph Kimong (Fakulti Psikologi dan Pendidikan, 2021)
Nowadays, binge-watching behavior marks a new era of TV-watching behavior among the young generation. Concerns about possible negative psychological factors that lead to this popular viewing pattern are discussed. The study investigates the relationship of depression and loneliness towards binge-watching behavior among Malaysian university students. It examines how depression and loneliness might influence binge-watching behavior. A total of 375 Malaysian university students had participated in this study. This study used three instruments: Beck Depression Inventory, Revised UCLA Loneliness Scale, and Binge-Watching Engagement and Symptoms Questionnaire. Findings showed that depression is significantly correlated with binge-watching behavior and affects it where it can be a predictor of binge-watching behavior. However, there was no significant correlation between loneliness and binge-watching behavior. The present study's findings will benefit future researchers as the obtained result clearly stated that depression had played a role in binge-watching behavior instead of loneliness. Therefore, more research is needed to examine binge-watching and its relations to other factors such as self-control, attachment, and well-being. Also, the expected consequences of binge-watching among Malaysian university students should be investigated as well.